Efeitos de exercícios de fortalecimento muscular específico sobre as medidas de sarcopenia, fragilidade e capacidade funcional de idosas comunitárias: um estudo quasi-experimental - Joana Ude Viana (2016)
Introduction: Frailty and sarcopenia are conditions that overlap and are considered geriatric syndromes because of their multifactorial etiology, high prevalece and imprecise diagnosis. Both are related to disabling outcomes such as reduced mobility, high risk of falls and fractures, hospitalization, poor quality of life and death. They still share difficulties in relation to their conceptualization and proper prevention and treatmentbecause of the lack of a consensus on these questions. It is known however, that progressive resistance training is able to prevent or counteract frailty and sarcopenia, minimizing their negative outcomes. On the other hand, there are still few studies about this intervention strtategy for the elder population, especially those sarcopenic and/or frail, mainly in Brazil, what demonstrate the need of researches on this theme. Objective: Verify the effects of a progressive resistance training on sarcopenia indicators (lean mass, muscle strength and physical performance), frailty (Fried et al. phenotype) and funcitonal capacity (Short Physical Perfomance Battery - SPPB) of community-dwelling sarcopenic elder women, comparing baseline and post 12 week intervention results. Method: the sample of study one was composed of 562 elder from FIBRA/Belo Horizonte. This is an epidemiological, cross-sectional, multidisciplinary and multicentric study elaborated to evaluate the frailty profile of Brazilian elder. Data from this sub-sample were used to establish, through Lee's predictive equation, possible cutoff points for Brazilian aged using the lowest 20% value above the mean for this population, as well as verify the associations among sarcopenia,incapacities and comorbidities. The sample from studies two and three was formed by 18 community-dwelling sarcopenic elder women, all allocated to an intervention group based on progressive resistance exercises for lower limbs. On study two the efficiency of the intervention on frailty and sarcopenia profiles transitions was assessed through paired t tests, as well as the correlations between frailty and sarcopeniaprofiles by Spearmans test. Study three verified the effects of the intervention with progressive resistance exercises on sarcopenia profile (muscle mass, strength and performance) of the elders, as well as their functional status through paired t tests. All analyzes were conducted using SPSS statistics program version 16.0 for Windows at significance level of =0.05 with confidence interval of 95%. Results: on study one,65.5% of the subjects were women with mean age of 74.15 ±6.43 years old, a negative correlation (r= - 0.081 and p= 0.05) between sarcopenia and instrumental activities of daily living (IADL) was found, besides a negative correlation between sarcopenia and comorbidities (r= - 0.103 and p= 0.014). In relation to the cutoff points determined to ascertain muscle mass measures according to Lees equation, the followingresults were found: < 6.47 kg/m2 for women and < 8.76 kg/m2 for men. Study two demonstrated that the intervention with progressive resistance training was able to enhance frailty and sarcopenia profiles reducing the number of frailty items (p=0.008, power = 0.81), increasing lean mass (p=0.003; power=0.90) assessed by densitometry (DXA) and demonstrating a positive significant correlation between bothsyndromes (r:0.60; p=0.009; power=0.99). On study three, significant changes were observed for muscle lean mass assessed by DXA (p=0.003; power= 0.90), muscle strength evaluated by handgrip strength (HGS) (p=0.001, power=0.49) and by isokinetic dynamometry through increases in power (p=0.001; power=0.98) and peak torque (p=0.001; power=0.96) variables at angular velocity of 60º/s, as well as improvingon functional capacity measured by SPPB (p= 0.001; power= 0.97). Conclusion: Progressive resistance exercises were able to enhance frailty and sarcopenia profile of elder women and have to be encouraged and implemented in public health programs aiming to retard the disablement process that occurs with these conditions improvingelders quality of life and reducing the burden related to these syndromes.